Volume 4: Cycle Innovations; Industrial and Cogeneration; Manufacturing Materials and Metallurgy; Marine 2009
DOI: 10.1115/gt2009-59451
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Coefficient of Friction for Representative and Predictive Finite Element Modelling of the Inertia Friction Welding

Abstract: Inertia friction welding is the process in which stored kinetic energy in a flywheel is converted to heat by relative sliding movement between surfaces of axi-symmetric components to achieve a weld in the solid-state. The work in this paper relates to the production of dual-alloy shafts for aeroengines. Frictional characteristics determine the conditions at the weld interface and these are controlled by rotational velocity and applied axial pressure. So-called representative and predictive methods have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The axial force is maintained after the flywheel comes to rest, allowing the metals to form a metallurgical bond [1]. Heat generation during the IFW process is dominated to a large extend by plastic deformation and frictional work which has been discussed previously by Mohammed et al [2]. On the other hand, heat transfer (HT) from workpieces involves conduction, convection, radiation and HT across the workpiece-die contact interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axial force is maintained after the flywheel comes to rest, allowing the metals to form a metallurgical bond [1]. Heat generation during the IFW process is dominated to a large extend by plastic deformation and frictional work which has been discussed previously by Mohammed et al [2]. On the other hand, heat transfer (HT) from workpieces involves conduction, convection, radiation and HT across the workpiece-die contact interface.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, heat transfer (HT) from workpieces involves conduction, convection, radiation and HT across the workpiece-die contact interface. HT by conduction within workpieces was considered in all previous finite element (FE) models developed for modelling the IFW process [2][3][4][5][6][7][8][9] where it is treated as 2D conduction problem in a radial system (eqn (1)). However the few that considered the remaining HT modes expressed contradicting opinions regarding their importance while there was no mention of values and methods implemented to account for it.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that peak temperature and strain rate are proportional to the applied pressure whereas the width of the heat affected zone (HAZ) is inversely proportional to the applied pressure. Mohammed et al (2009) built a coupled thermo-mechanical axisymmetric model of IFW of a dissimilar high strength steel and a nickel-based superalloy on DEFORM software package. The paper aims at evaluating the friction conditions which control the weld formation and are determined by weld parameters, mainly rotational speed and axial pressure.…”
Section: Numerical Modelling Of Metalsmentioning
confidence: 99%
“…Where 𝜀̅ is the effective strain rate, 𝜀v is the volumetric strain rate, 𝐹 is surface traction, u is the velocity, and 𝐾 ̅ is a penalty constant that avoids volume alteration by forcing a material incompressibility factor on the velocity field (Mohammed et al, 2009).…”
Section: Modelling Using Deform 2dmentioning
confidence: 99%
See 1 more Smart Citation